A genome-wide association study for highly sensitive cardiac troponin T levels identified a novel genetic variation near a RBAK–ZNF890P locus in the Japanese general population. (15th April 2021) - Nasu, Takahito; Satoh, Mamoru; Hachiya, Tsuyoshi; Sutoh, Yoichi; Ohmomo, Hideki; Hitomi, Sho; Taguchi, Satoru; Kikuchi, Hiroto; Kobayashi, Takamasa; Takahashi, Yuji; Osaki, Takuya; Morino, Yoshihiro; et al.
Abstract: Background: Cardiovascular disease (CVD) is a major cause of mortality worldwide. High-sensitivity cardiac troponin T (hs-cTnT) is released into the bloodstream due to cardiomyocyte damage and is associated with a high CVD risk. This study aimed to investigate hs-cTnT-related genetic variation and to examine whether this is an associated risk factor for CVD in the Japanese general population. Methods: This was a genome-wide association study (GWAS) based on a cohort from the 2013 Tohoku Medical Megabank Project community study. The GWAS was performed using a HumanOmniExpressExome BeadChip array with 914, 035 autosomal single-nucleotide polymorphisms. The Framingham Risk Score and the Suita score were used to evaluate the future risk of CVD. Results: The GWAS identified 10 loci reaching suggestive significance in the discovery cohort. A replication analysis confirmed that one of the 10 loci, rs7798496, is associated with elevated hs-cTnT levels. The combined P value in the discovery and replication cohorts for the association between the rs7798496 and hs-cTnT levels was 3.4 × 10 −8, which indicates that the novel variant reached genome-wide significance. The rs7798496 loci was located at an intergenic region between the retinoblastoma gene product (RB)-associated Krüppell-associated box (KRAB) zinc finger, zinc finger protein 890, and pseudogene (ZNF890P). Logistic regression analysis revealed that the presence of the rs7798496 T allele was strongly associated with a high risk for CVD. Conclusions: This study provides insights into a link between a novel genetic variant, T allele of rs7798269, and elevated hs-cTnT levels as a future risk for CVD in the general Japanese population. Highlights: Genome-wide association study on hs-cTnT levels was performed in the general Japanese population. The present study found that a novel genetic variant, the T allele of rs7798269 is associated with hs-cTnT levels in Japanese general population. The present study suggests that the T allele in rs7798496 may be associated with a high risk for CVD.